Advocacy for Religious Plurality in Vivekananda’s Speech (Saptagandaki Journal, 2022)
This research examines Swami Vivekananda’s speech delivered in the World Parliament of Religions in Chicago in 1893 AD. It has been evaluated in the light of Mortimer Jerome Alders’s Truth in Religion: Plurality of Religion and Unity of Truth. While evaluating Vivekanand’s advocacy for plurality of religions for the global peace and order, the researchers concerns on his resistance to religious fanaticism and orthodoxy. For the study of his resistance to the exploitation and extermination adopted by the westerners in the shield of religion calling it “Civilizing Mission”, the researcher takes his essay The East and the West as the major reference. The study argues that Vivekananda’s appeal for the celebration of religious plurality counters the bigotry and fanaticism in the name of religion. It is assumed that this article has a deep substance to understand Vivekanada’s advocacy for plurality of religions, emphasizing on the tenets of pluralism in Hinduism and historical repercussions of religious hegemony.